Investment in Indonesia After Constitutional Court’s Decision in the Review of Job Creation Law - Nurhayati, Yati; Mohd Zahir, Mohd Zamre; Ifrani, Ifrani; Komarudin, Parman (Lentera Hukum, 2022)
In 2021, the Indonesian Constitutional Court decided conditionally unconstitutional in the review of the Job Creation Law. It was among a few decisions made by the Constitutional Court to accept a formal review, even if some dissenting opinions followed it. While the decision has largely influenced a wide array of regulatory laws because the Job Creation Law adopts the omnibus law model, the pivotal issue in this paper rests on the legal basis for investment in Indonesia after this decision. Firstly, it enquired whether the Constitutional Court exceeded its power for a procedural judicial review against the Job Creation Law. Second, it discussed the legal basis for investment in Indonesia after the Constitutional Court's Decision No. 91/PUU-XVIII/2020. Using normative research, the results showed that with the conditional unconstitutional decision, the Indonesian investment world would experience legal uncertainty for the next two years, especially new businesses, licensing, and investments with the enactment of the Job Creation Law. In particular, if the legislative branch failed to improve this law over two years, businesses, licensing, and investments in Indonesia might have no legal basis, resulting in the uncertain situation of the government’s desire to realize the friendly investment.Keywords: Constituional Court, Job Creation Law, Judicial Review.